Benzyltrimethylammonium cadmium dicyanamide with polar order in multiple phases and prospects for linear and nonlinear optical temperature sensing. Issue 30 (16th July 2021) - Mączka, Mirosław; Gągor, Anna; Zaręba, Jan. K.; Trzebiatowska, Monika; Stefańska, Dagmara; Kucharska, Edyta; Hanuza, Jerzy; Pałka, Norbert; Czerwińska, Elżbieta; Sieradzki, Adam
Abstract : Benzyltrimethylammonium cadmium dicyanamide exhibits linear and nonlinear optical temperature sensing capability. Abstract : Coordination polymers with multiple non-centrosymmetric phases have sparked substantial research efforts in the materials community. We report the synthesis and properties of a hitherto unknown cadmium dicyanamide coordination polymer comprising benzyltrimethylammonium cations (BeTriMe + ). The room-temperature (RT) crystal structure of [BeTriMe][Cd(N(CN)2 )3 ] (BeTriMeCd) is composed of Cd centers linked together by triple dca -bridges to form one-dimensional chains with BeTriMe + cations located in void spaces between the chains. The structure is polar, the space group is Cmc 21, and the spontaneous polarization in the c -direction is induced by an arrangement of BeTriMe + dipoles. BeTriMeCd undergoes a second-order phase transition (PT) at T 1 = 268 K to a monoclinic polar phase P 21 . Much more drastic structural changes occur at the first-order PT observed in DSC at T 2 = 391 K. Raman data prove that the PT at T 2 leads to extensive rearrangement of the Cd- dca coordination sphere and pronounced disorder of both dca and BeTriMe + . On cooling, the HT polymorph transforms at T 3 = 266 K to another phase of unknown symmetry. Temperature-resolved second harmonic generation (TR-SHG) studies at 800 nm confirm the structural non-centrosymmetry of all the phases detected. Optical studies indicate that BeTriMeCd exhibits at low temperatures an intense emission under 266 nm excitation. Strong temperature dependence of both one-photon excited luminescence and SHG response allowed for the demonstration of two disparate modes of optical thermometry for a single material. One is the classic ratiometric luminescence thermometry employing linear excitation in the ultraviolet region while the other is single-band SHG thermometry, a thus far unprecedented subtype of nonlinear optical thermometry. Thus, BeTriMeCd is a rare example of a dicyanamide framework exhibiting polar order, SHG activity, photoluminescence properties and linear and nonlinear optical temperature sensing capability.